Effect of volatile reactions on oil production and composition in thermal and catalytic pyrolysis of polyethylene. (1st July 2020) - Chen, Zezhou; Zhang, Xurui; Che, Lei; Peng, Huanghu; Zhu, Shouxin; Yang, Fan; Zhang, Xu
Graphical abstract: Highlights: Yield and quality of the oil were investigated at various volatilization conditions. A high volatilization temperature favors cracking of volatiles to form light oil. Effect of volatilization time on oil is dependent on volatilization temperatures. Volatile reactions hardly affect the carbon distribution of the oil after catalysis. Alkenes are more than alkanes in oil and contribute to coke deposition on catalyst. Abstract: The volatiles generated from the pyrolysis of waste plastics undergo chemical reactions before being catalyzed to produce the plastic-derived oil. To reveal the relation between the oil properties and the volatile reactions, thermal and catalytic pyrolysis of polyethylene – a main component in waste plastics – were studied at volatilization temperatures of 300–600 °C with a volatilization time of 17.7–53.0 s in a two-stage reactor. The yield and composition of the oil in both thermal and catalytic reactions were investigated. It was found that in thermal pyrolysis, a high volatilization temperature favors the cracking of volatiles, resulting in the decline of carbon chain length and the decrease of the oil yield. Extension of the volatilization time favors the formation of light oil at a volatilization temperature above 400 °C, but produce more long-chain fractions at a volatilization temperature of 300 °C. The carbon number distribution of the oil after catalysis is independent on the conditions for volatile reactions, but the yields of the oil and each fraction after catalysis are higher at a lower volatilization temperature and shorter volatilization time. The long-chain alkenes in the volatiles is responsible for the formation of the coke deposited on catalyst.